Effect of glutathione on leakage of various enzymes from buck semen during freezing - SINHA, M P; SINHA, A K; PRASAD, R L (The Indian Journal of Animal Reproduction, 2023)
Semen samples from 12 bucks were extended in Tris dilutor with 2 and 5 mM of glutathione. The activities of acrosome, hyaluronidase, AKP, AST, ALT and LDH were assayed in equilibrated and frozen-thawed semen samples. Significantly (P < 0.01) higher intracellular activity of acrosin was recorded in semen samples extended with 5 mM of glutathione. Effect of glutathione on acrosin activity was significant at both the pre and post-freeze stage. Addition of 5 mM glutathione also decreased significantly the release of hyaluronidase, AKP, AST, ALT and LDH enzymes from the sperm cell in the medium.